Autonomia universitária controlada: o político e o jurídico-institucional na Universidade Estadual do Sudoeste da Bahia - Lima, Iracema Oliveira (Universidade Federal de São Carlos, 2008)
This paper presents the results of a research about the higher education public policy, developed by Bahia State Government since 1961 until 2000, as part of a economic development project, on the first sight, but also essentially politic, which aim was: inserting Bahia State in the same process of economic development, in progress, in the states of southeast region and at the same time to enlarge the political power of the dominant elite, in the countryside of Bahia. It was chosen this specific period of time because of the guidelines and background for the national education under the Law 4.024/61 and the higher education reform under the law 5.540/68 whose promulgation date from 1960's decade. Those laws are contemporaries to the beginning of current complex of public state universities from the State of Bahia. The 1990 s represented for the political history of the State a landmark for the reorganization of the State and for the educational policy. It was a decade rich in debates about the new law, 9.394/96, its guidelines and background for the national education. The research was oriented by a main question that was formulated on the following terms: how the Brazilian historical conditions were reflected in Bahia and how it made the government of Bahia start the incorporation and spreading process for the higher education, compliant to the legislation but with contradictions, and at the same time, organizing the set of Universities from the state without losing the political control over those institutions? The general aim of the research was to analyze the public policies for the higher education, elaborated from the political reorganization of the Brazilian state mediated in politics of the State of Bahia, capturing from this process, the contradiction that involves the discussion about expansion / organization of the state universities and political centralization. The adopted methodology was supported by documental analysis revealing about the conception the liberal state, inside the political reform, and how the State conceives the matter related with the autonomy university. It was also carried out a bibliographic research in order to trace the trajectory of the conception of the autonomy existent in the national debate, inter-relating them with main aspects like economical, political and social that justifies that trajectory. That historical analysis also observed the relationship of those movements with the development process of higher education in national level, mediated by the specificities of ―Enigma Baiano‖. It is attested at the end of the considerations that the politics from the State of Bahia have strategies that favor the centralization process of administrative management and they also block any action of decentralization, which should be avoided even in its inception. In this context is also presented the contradictory relationship between the local power and the State Government highlighting the historical specificities of each period and region in question.
Keywords: Educação; Autonomia universitária; Políticas públicas; Ensino superior; CIENCIAS HUMANAS::EDUCACAO